Evaluating smart manufacturing readiness: A maturity model perspective - Hammad, Muhammad Yahya; Syed Radzi, Rahamaddulla; Puteri Fadzline, Muhamad Tamyez; Azim Azuan, Osman; Ahmad Nazif, Noor Kamar (RSIS International, 2025)
The emergence of Industry 4.0 has transformed the manufacturing sector, necessitating established frameworks to appraise digital preparedness. To fill in the gaps in current models that ignore the particular obstacles faced by small and medium-sized businesses (SMEs) and urban manufacturing firms, this study suggests a customized Urban Smart Factory (USF) maturity model. The approach incorporates essential elements, including sustainability, resilience, digitalization, and workforce competencies, providing a thorough assessment of smart manufacturing preparedness. Key research trends were diagnosed by bibliometric analysis, and case studies from several manufacturing sectors were used to validate the suggested model. According to the findings, a large number of firms inadequately use the instruments necessary to evaluate workforce and technology readiness, which leads to irregular attempts at digital transformation. By offering an organized framework for distinguishing technology gaps, assessing organizational adaptability, and facilitating the creation of strategic roadmaps for Industry 4.0 adoption, the USF maturity model fills this gap. By highlighting the connections between technology, human capital, and administrative processes, the study advances our acquiesce of digital transformation in the urban manufacturing framework and adds to the theoretical conversation. The recognition of the model provides useful information for businesses perceiving to advance their digital maturity while negotiating the challenges of smart manufacturing. Future studies should concentrate on incorporating cuttingedge technology like blockchain and artificial intelligence while broadening the model's application through many businesses and geographical areas. Conclusively, our research creates the groundwork for manufacturing ecosystems that are robust, sustainable, and technologically sophisticated, spurring long-term growth and innovation.